Thursday

March 5, 2015

March 5, 2015

Posted by **Millers** on Monday, October 14, 2013 at 3:06pm.

- Calculus -
**Reiny**, Monday, October 14, 2013 at 3:29pmlet y = (1+9x)/(8-4x)

for inverse, interchange the x and y variables

x = (1+9y)/(8-4y)

now solve this for y .....

8x - 4xy = 1 + 9y

8x - 1 = 9y + 4xy

y(9+4x) = 8x-1

y = (8x-1)/(9+4x)

or**f^-1 (x) = (8x-1)/(9+4x)**

check with some arbitrary x

say x = -1

f(-1) = (1-9)/(8+4) = -8/12 = -2/3

f^-1 (-2/3)

= (8(-2/3) - 1)/(9 + 4(-2/3))

= (-19/3) / (19/3)

= -1 , as expected

"more than likely" my answer is correct.

**Answer this Question**

**Related Questions**

Calculus Help - The formula C =5/9(F − 32), where F ≥ −459.67...

Pre-calculus - Given the following values for f(t): t : f(t) 3 : -7 6 : 6 9 : 19...

math - The cost of producing q articles is given by the function C=f(q)=100+2q...

calculus - f(x) = (x+2)/(x+6) What is f^(-1)(-6)? (what is f inverse of -6) I ...

pre calculus - Find the inverse of the function below. Graph the function below ...

Calculus - Given the function" f(x)=1/4x− 3, find a formula for the ...

calculus - Find a formula for the inverse of the function f(x) = (4 x-1)/(2x+3)

Pre-Calculus - Find the inverse function for the function f(x)=2^(x)+1/2^(x)-1 ...

Algebra - Dan works at a hardware store. The employee discount is determined by ...

math - Could you show me step by step how to find the inverse of this problem: ...